Relationship on residents perception between quality of air and perceived health at PPR Desa Tun Razak / Azureen Kharuddin - Kharuddin, Azureen (2022)
Air is one of the most important components and is naturally available for humans. However, most of us seem to take it for granted by carelessly polluting the air. Multiple human activities have badly influenced the environment. Deteriorating air quality has affected people’s health caused by the widespread of air pollution. The main question is whether the people aware of the poor air quality in their residential areas. Is the quality of air capable to affect the perceived health, especially in low-cost high-rise residences? Therefore, assessment and measurements should be carried out in the area of high-rise and low-cost houses. Thus, this study aims to analyze the relationship between the residents’ perception of air quality and perceived health in PPR Desa Tun Razak. There are four (4) research objectives in this study including 1) to determine the outdoor quality of air at PPR Desa Tun Razak; 2) to observe the current quality of air issues at PPR Desa Tun Razak; 3) to identify the resident’s perception towards the quality of air at PPR Desa Tun Razak; 4) to analyze the relationship between the quality of air and perceived health at PPR Desa Tun Razak. All the objectives were achieved through the fieldwork measurement, observation, and set of questionnaires distributed to the residents of PPR Desa Tun Razak, Kuala Lumpur.